Determination of the ORC-RO system optimum parameters based on 4E analysis; Water–Energy-Environment nexus. (1st March 2019) - Shayesteh, Ali Akbar; Koohshekan, Omid; Ghasemi, Amir; Nemati, Mohammad; Mokhtari, Hamid
Graphical abstract: Highlights: Introduction of the environmental impacts index on RO system. Choosing the optimum configuration and ORC fluid from 4E+D point of view. The benefit of low grade heat losses to reduce the environmental impacts of RO. Water-Energy-Environmental nexus. Abstract: This paper presents the concentration disposal index (CDI) concept extension for increasing the Water–Energy-Environmental nexus and reducing the environmental impacts of RO system brine. This non-dimensional index introduces the difference between the density of brine flow and raw water tank in recovery. This concept is utilized in main engine system of the ship. Different configurations of Organic Rankine Cycle (ORC) and working fluids are studied at the outlet of high temperature thermal source (280 °C), based on Energy analysis (1E), Exergy (2E), Economic (3E) and environmental impacts (4E) in order to produce desalinated water (4E+D). The output power from ORC is used as the driver of RO high pressure pump. Based on the waste heat in system, the sources are used for preheating of RO system pump inlet water. These sources are: Lubricating oil, air cooler and jacket cooler and ORC condenser. The key parameters in optimization are: (1) the ORC configuration choice, (2) the working fluid of Rankine cycle based on thermal source, (3) the RO system optimum design, (4) the membrane selection among the DOW company membranes, (5) the pinch and approach temperatures of the Waste Heat Recovery (WHR), (6) the reduction of environmental impacts of RO brines, (7) the selection of Energy Recovery Device (ERD). Determination of these parameters is done according to system optimization by genetic algorithm (GA). In order to consider the CDI function impact, once the system is considered with two objectives based on exergy efficiency of the entire cycle and the unit product cost (UPC) and then is considered by three objectives; the two mentioned ones and the CDI function. The results of these two optimizations indicate that, utilizing CDI reduces the ultimate concentration of the brine and increases the buoyancy force for faster mixture. In three-objective optimization, the ORC configuration is chosen with the recuperator, the R245ca working fluid, the two-stage RO system and the SW30XLE-400i membrane for both of stages.